Effect of the application of circularity requirements as guided questions on the creativity and the circularity of the design outcomes. (25th January 2021) - Ruiz-Pastor, Laura; Mulet, Elena; Chulvi, Vicente; Royo, Marta
Abstract: Implementation of the circular economy is beginning to become a reality and the early stages of product design are crucial for a proper adoption of the circular model. However, several studies claim that sustainability requirements usually decrease creativity. Therefore, it is necessary to help designers to think in a more circular manner and, at the same time, not compromising the creativity. In this research, we study if creativity and circularity of the design outcomes change depending on whether circular requirements are applied as guided questions during the idea generation. For this purpose, an experiment has been carried out in which 20 engineering design students' teams propose a novel idea for a product. Half of the teams received some circular economy requirements in the form of explicit guided questions, while the other half did not. The novelty, usefulness and feasibility of the design outcomes are assessed to measure creativity. Circularity is determined by accounting the number of items to slow, close and narrow loops at each design proposal. The results indicate that explicitly introducing guided questions leads to no significant differences in creativity or circularity. However, it does lead to more dispersed circularity results. So, applying circular requirements explicitly in the form of guided questions does not worse creativity in comparison to when these requirements are implicit. This work offers new results on the effect of circular requirements in the generation of ideas. These findings are useful for the management of design teams in companies and also for design teaching. Highlights: It's necessary to introduce circular economy into creative product design. Designers need guidance to introduce circularity in the conceptual design stage. The type of guidance may vary circularity and creativity of the design outcomes. In the fulfilled experience, the requirements were implicit or by guided questions. Results point to differences in creativity and circularity results provided.